The Role of Inclusive Political Education for Persons With Disabilities in Realized Equal Political Participation in Indonesia - Della Rahmadania Ningrum; Sunarso Sunarso (Riviera Publishing, 2025)
People with disabilities who have physical, mental, and emotional limitations often face discrimination and negative perceptions, resulting in unequal political participation and disparities between them and other members of society. The objectives of this article are 1) to describe the important role of inclusive political education for people with disabilities in achieving equal political participation and 2 ) to analyze the various challenges and obstacles in inclusive political education for people with disabilities in achieving equal political participation. The method used is a literature review, with data sources including books, journals, and supporting websites. Inclusive political education is in line with the diversity of Indonesian society, especially for persons with disabilities as a marginalized group. Inclusive political education will ensure that everyone has equal opportunities without discrimination by any group, including persons with disabilities. Several aspects that need to be considered in inclusive political education for people with disabilities include detailed and interactive modules, interesting and accessible methods, adequate facilities and infrastructure, experience-based learning, extensive and regular discussion forums, and cross-sector collaboration. High political participation among people with disabilities will ensure their equal status with other members of society.